2013
DOI: 10.1016/j.envpol.2012.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of metals in road-deposited sediment along an urban–rural gradient

Abstract: a b s t r a c tWe applied the traditional risk assessment methods originally designed for soils and river sediments to evaluation of risk associated with metals in road-deposited sediment (RDS) along an urbanerural gradient that included central urban (UCA), urban village (UVA), central suburban county (CSA), rural town (RTA), and rural village (RVA) areas in the Beijing metropolitan region. A new indicator RI RDS was developed which integrated the RDS characteristics of mobility, grain size and amount with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(68 citation statements)
references
References 40 publications
1
67
0
Order By: Relevance
“…We found that places that had higher RDS masses per unit area also had higher proportions of relatively coarse particles. We assigned comparatively low values to the higher RDS masses per unit area because coarser particles give lower levels of risk associated with their metal contents and the mobility of those metals (Zhao and Li, 2013). Metals associated with RDS were ranked by comparing the measured concentrations of the metal of interest with its background concentrations.…”
Section: Ranking the Source And Transport Factor Ratingsmentioning
confidence: 99%
See 3 more Smart Citations
“…We found that places that had higher RDS masses per unit area also had higher proportions of relatively coarse particles. We assigned comparatively low values to the higher RDS masses per unit area because coarser particles give lower levels of risk associated with their metal contents and the mobility of those metals (Zhao and Li, 2013). Metals associated with RDS were ranked by comparing the measured concentrations of the metal of interest with its background concentrations.…”
Section: Ranking the Source And Transport Factor Ratingsmentioning
confidence: 99%
“…We assigned weightings to the source and transport factors according to our in situ investigations into the RDS characteristics. The RDS mass per unit area was ranked into six levels (M weighted ), in which 0e30 g/m 2 was given a value of 1.00, 31e60 g/m 2 a value of 1.75, 61e90 g/m 2 a value of 2.50, 91e140 g/m 2 a value of 3.00, 141e190 g/m 2 a value of 3.50, and >190 g/m 2 a value of 3.75 (Zhao and Li, 2013). The RDS mass per unit area ranking levels were primarily based on the results of our in situ investigation into the RDS mass per unit area (using a total of 167 sites, 97 of which were from areas on main roads and 70 of which were in residential areas), because no standard values are available for dividing RDS masses per unit area into levels.…”
Section: Ranking the Source And Transport Factor Ratingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the original evaluation index classifi cation was adjusted according to the number of pollutants and the ratio of the toxicity coeffi cient of each element. The degree of ecological risk was classifi ed as low ecological risk (E i < 15, RI < 50), moderate ecological risk (15 ≤ E i < 30, 50 ≤ RI < 100), considerable ecological risk (30 ≤ E i < 60, 100 ≤ RI < 200), high ecological risk ( 60 ≤ E i < 120, RI ≥ 200) and very high ecological risk (E i ≥ 120) (Lu et al 2014;Zhu et al 2008;Zhao and Li, 2013).…”
Section: Environmental Risk Assessment Of Heavy Metals In Street Dustmentioning
confidence: 99%